2015
DOI: 10.1111/jai.12683
|View full text |Cite
|
Sign up to set email alerts
|

A combination of corn gluten and soybean meal as a substitute for fishmeal in diets of turbot (Scophthalmus maximusLinnaeus, 1758) in brackish water

Abstract: This study was conducted to test the replacement of fishmeal (FM) with a combination of corn gluten meal (CGM)-soybean meal (SBM) (at a ratio of 58 : 42, respectively) fortified with lysine, taurine and monocalcium phosphate (MCP) in turbot (Scophthalmus maximus) diets. FM as the main protein source in the control diet (FM100) was replaced in 15% decrements while increasing the combination of replacement material: 85% FM (FM85), 70% FM (FM70), 55% FM (FM55) and 40% FM (FM40). The diets were fed to triplicate g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
12
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(15 citation statements)
references
References 16 publications
1
12
2
Order By: Relevance
“…This is in contrast to previous studies which reported a DFI decrease when plant feedstuff was used at comparable substitution levels (Bai et al, ; Bonaldo et al, ; Fuchs et al, ; Gu et al, ). However, there are also investigations that detected no significant decrease in DFI (Sevgili et al, ; Yun et al, ). According to Bonaldo et al and Chen et al (), the application of SBM in aquafeeds leads to a reduced consumption of the diet and thus limited growth performance.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…This is in contrast to previous studies which reported a DFI decrease when plant feedstuff was used at comparable substitution levels (Bai et al, ; Bonaldo et al, ; Fuchs et al, ; Gu et al, ). However, there are also investigations that detected no significant decrease in DFI (Sevgili et al, ; Yun et al, ). According to Bonaldo et al and Chen et al (), the application of SBM in aquafeeds leads to a reduced consumption of the diet and thus limited growth performance.…”
Section: Discussionmentioning
confidence: 95%
“…This is in line with the findings of several other studies on turbot. Here, growth performance and feed conversion were negatively affected by the administration of various plant proteins in general (Fournier, Huelvan, & Desbruyeres, ; Nagel et al, ) or SBM and mixtures of both in particular (Bai et al, ; Bonaldo et al, , ; Gu et al, ; Sevgili et al, ; Yun, Mai, Zhang, & Xu, ).…”
Section: Discussionmentioning
confidence: 99%
“…Plant protein is deficient in taurine, which is in conjugation with bile acids, osmoregulation and cell membranes (NRC, ). Sevgili et al () found that taurine‐fortified plant protein diets (mixture of soybean meal and CGM) were able to replace higher level of FM protein in turbot ( Scophthalmus maximus Linnaeus, 1758). In summer flounder ( Paralichthys dentatus ), replacing FM with SBM alone and mixture of SBM, CGM and CPC with or without IAA supplementation obtained similar growth performance; however, a blend of the plant proteins with taurine supplementation caused significantly higher growth performance (Enterria et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…The lipid contents in muscle and whole body were unaffected in the present study, but high carbohydrate content might be the main reason for fish fed the CGM diets having significantly higher intraperitoneal fat ratio values than that of fish fed PPI diets. However, high inclusion of CGM‐SBM reduced whole body lipid content in trout (Sevgili et al, ). Whole body ash content decreased with increasing dietary PPI content in tilapia (Schulz et al, ), and replacing 50% FM with LPC, PPC and their mixtures caused lower whole body ash content of black sea bream (Zhang, Øverland, Xie, et al, ).…”
Section: Discussionmentioning
confidence: 99%
“…Corn gluten is a low priced PP material and contains a minimum of 60% protein (Morales et al, 1994) which is 96% digestible for turbot (Fournier et al, 2004). Corn gluten can substitute up to 30% of FM without negative effects on growth or FCR in turbot (Sevgili et al, 2015). Soybean products are generally high in protein content, ranging from 45% in soybean meal to 70% and more in soy protein concentrate.…”
Section: Introductionmentioning
confidence: 99%